Wirksamkeit der Förderung der beruflichen Weiterbildung vor und nach den Hartz-Reformen - Holger Bonin; Hilmar Schneider (Institute for the Study of Labor (IZA), 2006)
This paper analyzes the effectiveness of occupational training programs for the unemployed before and after the substantial amendments in German labor market legislation known as Hartz reforms. Based on the official evaluation of the reforms, we show that program impacts vary much across different types of training. Before the reform, especially long-term training to a new occupation was not effective. It appears that the effectiveness of most training measures has substantially improved after the reform. This is due to the introduction of better quality management, stronger competition among the suppliers of training, and more freedom of choice for the unemployed.
Keywords: J68; H43; D61; 330; program evaluation; occupational training; Hartz-Reforms; Germany; Beschäftigungspolitik; Betriebliche Weiterbildung; Weiterbildung; Wirkungsanalyse; Deutschland